Application of the Schlumberger Configuration Geoelectric Method to Identify the Distribution of Aquifers in Klampok Village, Singosari Sub-District, Malang Regency - Muh. Aimar Al Qadri R; Vita Ayu Kusuma Dewi; Mohammad Musthofa Al Ansyorie (Rekayasa Sipil, 2024)
Water demand always increases rapidly, which is in line with the increase in population over time. One alternative for providing fresh water is groundwater usage. Klampok Village is one village affected by freshwater problems, especially during the dry season. The current solution in the form of water supply from the government is still insufficient to meet the water needs of residents, most of whom work in the agricultural and plantation sectors. This problem can be overcome by searching for new groundwater locations using geoelectric methods. The geoelectric method utilized the Schlumberger configuration and Vertical Electrical Sounding (VES) to conduct a field test. Field test results were then processed using IPI2Win. The Root-Mean-Square (RMS) result was 1.94% by identifying eight layers. The research finding is resistivity values of 11.38 - 2167 with a depth of 100 meters.